Masters of the Nefarious mollusk rampage - La Police, Pierre 1959- (The New York Review of Books, 2024)
"A tsunami slams into the Maluku islands. Giant mollusks wreak havoc. An ominous, quadrilateral UFO appears in the night sky. And a mysterious villain watches and waits in the shadows... Twin paranormal investigators, Montgomery and Chris, and their best friend, Fongor, are on the case, delving into this unduly complicated and possibly nefarious plot. They're the only ones who can unravel the mystery, but they might not--especially if they can't stay on task. Between journeys to Uganda, primordial Earth, and the pants store, and confrontations with ghosts frozen in ice cubes, baby turtles, and an army of small, sinister men, the trio will be tested like never before as they search for clues, answers, and a good all-you-can-eat buffet spot. Finally in English, Pierre La Police's Masters of the Nefarious is one of his funniest and most irreverent comics, an unpredictable adventure pastiche that will leave you laughing to the final explosive face- (and pants-)off"--
Keywords: Ermittlung; Geist; UFO; Tsunami; Paranormales Erlebnis; Molukken; Tsunamis / Comic books, strips, etc; Paranormal comics; Graphic novels; Comic; Humorous comics; Comics (Graphic works)